Application of the Istishna' Agreement to Online Buying Or Selling Transactions from an Islamic Perspective - syahfira, hermalia; Rayyan Firdaus (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
As time goes by, technology in carrying out transactions is also developing, making it easier for people to buy and sell. Like selling online or often called E-commerce. So that currently we can buy and sell online as we often encounter, namely on the Shopee application, Tokopedia Lazada group, TikTok Shop, Instagram, Facebook marketplace, Amazon, Alibaba group, jd.com, Walmart, Shopify, Coupang. In online buying and selling (E-commerce), there is a contract used, namely the Istisna' contract. The aim of this research is to deepen the istishna' agreement regarding E-commerce from an Islamic perspective. This paper uses qualitative methods with a phenomenological approach. The analysis used is narrative analysis, so that we can get to know the information in E-commerce in more detail. The results of this research are so that we can find out how Islamic buying and selling transactions occur in istishna' contracts, the basis of sharia, and how istishna' transactions are formed.